2017
DOI: 10.1155/2017/3658247
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance of the Microwave Absorbing Materials by Using Dielectric Resonator Arrays

Abstract: We present a technique for enhancing the performance of microwave absorbing materials in terms of weight, thickness, and bandwidth. The introduced technique is based on fabricating the microwave absorbing (MA) material in a structure comprised of an array of circular cylinder dielectric resonators (CDR) backed by a perfect electric conductor (PEC) ground plane. Numerical electromagnetic methods are employed to study the properties of the proposed MA array structures, where 3D full wave simulation using finite-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Authors have concluded that a flat layer of nanopowdered Fe 20 Ni 8 material with thickness of 5 mm backed by perfect electric conductor (PEC) shows reflection loss (RL) peak as low as − 50 dB and 3 GHz 10-dB bandwidth, whereas the same material when shaped into MA-CDR array, of height of 4 mm can achieve as low as − 50 dB RL peak and 12 GHz 10-dB RL bandwidth. However, the performance as well as thickness can be improved using CDR structures with advanced materials [75].…”
Section: Geometry-based Absorbersmentioning
confidence: 99%
“…Authors have concluded that a flat layer of nanopowdered Fe 20 Ni 8 material with thickness of 5 mm backed by perfect electric conductor (PEC) shows reflection loss (RL) peak as low as − 50 dB and 3 GHz 10-dB bandwidth, whereas the same material when shaped into MA-CDR array, of height of 4 mm can achieve as low as − 50 dB RL peak and 12 GHz 10-dB RL bandwidth. However, the performance as well as thickness can be improved using CDR structures with advanced materials [75].…”
Section: Geometry-based Absorbersmentioning
confidence: 99%
“…As devices designed to effectively absorb incident electromagnetic radiation by transforming it into ohmic heat or other forms of energy, electromagnetic (EM) wave absorbers are often used for shielding (Ahmad et al, 2019). The operating frequencies of EM absorbers previously demonstrated have covered the microwave band (Al-zoubi & Naseem, 2017;H. Chen et al, 2018;M.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with EM shielding material, microwave-absorbing materials (MAM) are powerful alternatives to eliminate pollution due to their effectiveness in dissipating microwave energy without any secondary pollution. In general, MAM and microwave-absorbing structures should satisfy general requirements that are enlisted as follows: it should (i) minimize the reflection of EM waves at the air to absorber interface; (ii) have strong absorption of EM waves; (iii) have broad bandwidth and angular response; (iv) have low weight and thickness [4]. Unfortunately, meeting these competing requirements simultaneously is a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, meeting these competing requirements simultaneously is a challenging task. To meet these objectives and enhance the efficiency of MAM, tedious and extensive techniques have been suggested [4]. These techniques can be categorized into two main categories: material and geometry based.…”
Section: Introductionmentioning
confidence: 99%